Front Cover. Issue 11 (23rd October 2018) - Padró, Julian; Lambertucci, Sergio A.; Perrig, Paula L.; Pauli, Jonathan N.
Abstract : The cover image is based on the Biodiversity Research Evidence of genetic structure in a wide‐ranging and highly mobile soaring scavenger, the Andean condor, https://doi.org/10.1111/ddi.12786 . Photo Credit: Gonzalo Ignazi.